CMA-Based Quadruple-Cluster Leaf-Shaped Metasurface-Based Wideband Circularly-Polarized Stacked-Patch Antenna Array for Sub-6 GHz 5G Applications - Supreeyatitikul, Nathapat; Janpangngern, Pisit; Lertwiriyaprapa, Titipong; Krairiksh, Monai; Phongcharoenpanich, Chuwong (My University, 2023)
This research proposes a quadruple-cluster leaf-shaped metasurface (MTS)-based circularly-polarized (CP) stacked-patch antenna array with hybrid coupler feed network for sub-6 GHz 5G applications. In the study, the leaf-shaped MTS-based CP stacked-patch antenna is characterized by characteristic mode analysis (CMA). In the antenna design, one cluster of the quadruple-cluster leaf-shaped MTS-based antenna array consists of 4×4 leaf-shaped MTS elements; and the hybrid coupler feed network is used to enhance impedance bandwidth (IBW), axial ratio bandwidth (ARBW), and antenna gain. Simulations are carried out and an antenna prototype is fabricated and experiments undertaken. The measured IBW, ARBW, and maximum gain at the center frequency (4 GHz) are 62.5% (3.4- 5.9 GHz), 21% (3.8- 4.54 GHz), and 9.04 dBic at 3.9 GHz. The novelty of this research lies in the use of: (i) the CMA concept to design and develop the leaf-shaped wideband MTS-based stacked-patch antenna with CP radiation pattern; and (ii) a low-complexity hybrid coupler feed network to enhance the IBW, ARBW and gain.
Keywords: Antenna arrays; characteristic mode analysis; couplers; metasurfaces; wideband